High-sensitivity measurements of strontium isotopes in polar ice - Burton, Graeme; Boutron, C.; Rosman, Kevin (Elsevier, 2002)
Techniques have been developed to measure the isotopic composition and concentration of Sr at sub-nanogram per gram levels in polar snow and ice samples. A 84Sr spike was used to determine Sr concentrations on a single sample aliquot of a few millilitre. Microlitre scale columns of Sr-Spec resin were used to purify Sr samples. Thermal ionisation mass spectrometry (TIMS) was used to measure the Sr isotopic ratios. A single TIMS measurement of the Sr sample yielded both isotopic composition and concentration after deconvolution of spike and sample spectra. This allows isotopic variations in Sr to be used to identify source regions of crustal dust. Early Holocene and last glacial maximum ice core samples from both Antarctica and Greenland were analysed to demonstrate the applicability of the technique. Sr isotopes were analysed in 20 g sized samples of Antarctic early Holocene ice where the concentration was only 31 pg g−1. This represents an improvement of two orders of magnitude in sample consumption over previous studies allowing for a much higher time resolution in the analysis of polar ice cores.